2021
DOI: 10.1002/ppul.25622
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function of healthy Korean children from three independent birth cohorts: Validation of the Global Lung Function Initiative 2012 equation

Abstract: Background and Objective Global Lung Function Initiative (GLI) 2012 equations were developed to resolve the age‐related disparity in interpreting spirometry results. Local validation of the equation is needed, especially in Northeast Asian children. This study evaluated the GLI equation in Korean children. Methods Spirometry indices (FEV1, FVC, FEV1/FVC, and FEF25%–75%) and clinical information were gathered from three population‐based birth cohorts. Predicted GLI reference values and z scores of spirometry re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
2
4
1
Order By: Relevance
“…increased dysanapsis) for children considered overweight and obese [ 9 ]. In line with our findings, previous studies have described associations between BMI and GLI-based lung function z-scores in children [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…increased dysanapsis) for children considered overweight and obese [ 9 ]. In line with our findings, previous studies have described associations between BMI and GLI-based lung function z-scores in children [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…This aligns with our findings and may be due to asymmetric lung growth (i.e., increased dysanapsis) for children considered overweight and obese [9]. In line with our findings, previous studies have described associations between BMI and GLI-based lung function z-scores in children [40,41]. P values for a trend in z-scores across ordered categories of BMI were <0.001 for FEV1, 0.014 for FVC, <0.001 for FEV1/FVC, and <0.001 for FEF25-75.…”
Section: Comparison With Other Studiessupporting
confidence: 93%
“…As the GLI-2012 equation17 for North East Asian ethnicity was developed using only subjects aged ≥16 years, the spirometry z-scores for young children in this study22 were calculated using extrapolation, which may have inadvertently inflated the effect sizes. This inference was partially supported by a validation study31 which found that South Korean females aged 7–8 years have mean FEV 1 and FVC z-scores lower than the GLI-2012 predictions by −0.23 (95% CI −0.31, –0.15) and −0.26 (95% CI −0.36, –0.16), respectively, suggesting the actual lung function for this subgroup is slightly below established baseline. A secondary analysis which excluded this outlier study22 from the meta-analyses yielded an alternative random-effects model for FEV 1 based on three studies with reduced statistical heterogeneity (red diamond; figure 2).…”
Section: Discussionmentioning
confidence: 88%
“…As the GLI-2012 equation 17 for North East Asian ethnicity was developed using only subjects aged ≥16 years, spirometry z-scores for this study 22 were calculated using extrapolation for young children, which may have inadvertently inflated effects sizes. This inference was partially supported by a validation study 31 which found that South Korean females aged 7-8 years have mean FEV 1 and FVC z-scores lower than GLI-2012 predictions by -0.23 (95% CI: -0.31, -0.15) and -0.26 (95% CI: -0.36, -0.16) respectively, suggesting actual lung function for this subgroup is slightly below established baseline. A secondary analysis which excluded this outlier study 22 from meta-analyses yielded an alternative random-effects model for FEV 1 based on three studies with reduced statistical heterogeneity (red diamond; Figure 2).…”
Section: Discussionmentioning
confidence: 88%